Effect of tooth-bleaching on the carbonate concentration in dental enamel by Raman spectroscopy - Vargas Koudriavtsev, Tatiana (2017)
BACKGROUND: There are not many studies evaluating the effects of surface treatments at the molecular level. The aim of this in vitro study was to analyze the concentration of carbonate molecules in dental enamel by Raman spectroscopy after the application of in-office and home whitening agents. MATERIAL AND METHODS: Sixty human teeth were randomly divided into six groups and exposed to three different home bleaching gels (Day White) and three in-office whitening agents (Zoom! Whitespeed and PolaOffice) according to the manufacturer´s instructions. The concentration of carbonate molecules in enamel was measured prior to and during the treatment by means of Raman spectroscopy. Statistical analysis included repeated measures analysis of variance (p≤0.05) and Bonferroni pairwise comparisons. RESULTS: At home bleaching agents depicted a decrease in the carbonate molecule. This decrease was statistically significant for the bleaching gel with the highest hydrogen peroxide concentration (p≤0,05). In-office whitening agents caused an increase in carbonate, which was significant for all three groups (p≤0,05). CONCLUSIONS: In-office bleaching gels seem to cause a gain in carbonate of the enamel structure, whilst at-home whitening gels caused a loss in carbonate.